PENGARUH FRAKSI VOLUME SERAT SABUT KELAPA DENGAN INTI SERBUK GERGAJI KAYU SENGON TERHADAP KEKUATAN BENDING KOMPOSIT HYBRID SANDWICH - Salman Salman; Muhammad Fajar; Muhammad Hazmi (Jurnal Teknologi, 2023)
The use of composites from hybrid materials requires further research in particular with respect to their mechanical properties. The purpose of this research was to know the effect of volume fraction of fiberglass and coconut husk to the bending strength of composite sandwich hybrid. The main ingredients of this research were sengon sawdust as a composite core, fiberglass and coconut husk, with unsaturated polyester resin as matrix. Specimens were prepared with varying volume fractions of 10%, 20% and 30% for skins of fiberglass and coconut fiber and then were tested with bending tests. The results showed that the greater the volume fraction, the greater the bending strength beside that it also reduced the failure of the composites.